An Act Declaring the Illegality of the Proceedings against [...] and for reserving and making null and void the said judgments, and all proceedings thereon (Printed by William Bradford, printer to Queens most Excellent Majesty, 1703)
Vacation of judgment against Nicholas Bayard and John Hutchins for treason by Lord Cornbury.